A CROSS-SECTIONAL STUDY OF TYPE 2 DIABETES MELLITUS PREVALENCE AMONG THE INDIAN RURAL POPULACE IN BIHAR. - Jha, Sudhir Chandra; Kumar, Naween; Kumar, Purushottam; Yadav, Amit Kumar (Student's Journal of Health Research Africa, 2023)
Background: Diabetes is difficult to manage in resource-poor countries like India, where many people are diagnosed late and have complications. This study seeks to increase diabetes research in rural India. The main goal of this study is to ascertain the incidence of Type 2 diabetes mellitus among rural populations in Bihar, India, who are 25 years of age and older. Methods: During the study, health camps were held and went door-to-door to determine rural diabetes prevalence. Fasting capillary blood glucose was tested with a glucose meter. All adults then consumed 75 g of glucose dissolved in 200 milliliters of water in five minutes. Two hours after intake, post-load capillary blood glucose was measured. Diabetes was confirmed by collecting blood samples in a fluorine vacutainer, with fasting plasma glucose levels ≥126 mg/dl and/or 2-hour postprandial glucose levels ≥200 mg/dl as diagnostic criteria. Results: According to the survey, 7.03% of rural residents had Type 2 diabetes; females had a greater prevalence of the disease (56%) than males (44%). Diabetes affected 28% of participants over the age of 70, compared to 11% of those in the 25–39 age range. Furthermore, 34.77% of diabetics were newly diagnosed cases, while 8.04% of participants had a prediabetic diagnosis. Conclusions: This study shows an elevated incidence of Type 2 diabetes in rural Bihar, India. Rural areas need comprehensive early diagnosis, care, and diabetes prevention education to meet this growing health burden. Recommendation: Early detection, management, and preventative education are crucial in rural western Uttar Pradesh, where Type 2 diabetes is common. Community-based awareness initiatives and accessible healthcare can lessen diabetes complications in the region.